An Entomological Investigation during a Recent Rift Valley Fever Epizootic/Epidemic Reveals New Aspects of the Vectorial Transmission of the Virus in Madagascar - Luciano Michaël Tantely; Soa Fy Andriamandimby; Maminirina Fidelis Ambinintsoa; Manou Rominah Raharinirina; Jean Théophile Rafisandratantsoa; Jean-Pierre Ravalohery; Aina Harimanana; Nirina Nantenaina Ranoelison; Judickaelle Irinantenaina; Miamina Fidy Ankasitrahana; Dany Bakoly Ranoaritiana; Laurence Randrianasolo; et al. (Pathogens, 2024)
A Rift Valley fever (RVF) outbreak occurred in at least five regions of Madagascar in 2021. The aim of this study was to provide an overview of the richness, abundance, ecology, and trophic preferences of mosquitoes in the Mananjary district and to investigate the distribution of mosquitoes that were RT-PCR-positive for RVFV. Three localities were prospected from 26 April to 4 May 2021, using light traps, BG-Sentinel traps baited with an artificial human odor, Muirhead-Thomson pit traps, and indoor pyrethroid spray catches. A total of 2806 mosquitoes belonging to at least 26 species were collected. Of 512 monospecific pools of mosquitoes tested with real-time RT-PCR, RVFV was detected in 37 pools representing 10 mosquito species. The RVFV-positive species were as follows: Aedes albopictus, Ae. argenteopunctatus, Anopheles coustani, An. gambiae s.l., An. mascarensis, An. squamosus/cydippis, Culex antennatus, Cx. decens, Cx. Tritaeniorhynchus, and Uranotaenia spp. Of the 450 tested engorged females, 78.7% had taken a blood meal on humans, 92.9% on cattle, and 71.6% had taken mixed (human–cattle) blood meals. This investigation suggests the potential role of mosquitoes in RVFV transmission within this epizootic/epidemic context and that the human populations at the three study sites were highly exposed to mosquitoes. Therefore, the use of impregnated mosquito nets as an appropriate prevention method is recommended.